2012
DOI: 10.1111/j.1755-3768.2012.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of epigallocatechin‐3‐gallate against N‐methyl‐D‐aspartate‐induced excitotoxicity in the adult rat retina

Abstract: ABSTRACT.Purpose: Epigallocatechin-3-gallate (EGCG), the major polyphenol of green tea, has been suggested to reduce glutamate excitotoxicity. We therefore investigated the potentially protective effects of EGCG against N-methyl-d-aspartate (NMDA)-induced excitotoxicity in the retina. Methods: Female Wistar rats (n = 171) were divided into a normal control group (n = 9); saline control group with intravitreal saline injections (n = 54); NMDA control group with an intravitreal NMDA injection and intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…EGCG is one of the most active major polyphenols of green tea and it is the constituent primarily responsible for the health benefits of drinking green tea. Recent research has shown that EGCG protects the retina against NMDA‐induced excitotoxicity and reduces retina ischemia/reperfusion injury by attenuating nitric oxide synthase activity . According to our data, the intravitreal treatment of CGA and coffee metabolites, CA and DHCA, had a stronger protective effect on RGCs than EGCG at the same dose (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…EGCG is one of the most active major polyphenols of green tea and it is the constituent primarily responsible for the health benefits of drinking green tea. Recent research has shown that EGCG protects the retina against NMDA‐induced excitotoxicity and reduces retina ischemia/reperfusion injury by attenuating nitric oxide synthase activity . According to our data, the intravitreal treatment of CGA and coffee metabolites, CA and DHCA, had a stronger protective effect on RGCs than EGCG at the same dose (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, animal models of NMDA-induced retinal cell degeneration, such as intraocular NMDA injection, glutamate transporter or specific NMDAR deficit mice, are useful models of RGC loss not only for drug discovery research [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], but for research into the regeneration of RGC [ 36 , 37 ]. For example, we have attempted retinal regeneration by transplantation of human embryonic stem cells after RGC loss induced by NMDA injection [ 38 , 39 ].…”
Section: Nmda-induced Retinal Ganglion Cell Degenerationmentioning
confidence: 99%
“…This indicated that EGCG might favorably influence inner retinal function in eyes with early to moderately advanced glaucomatous damage. In our previous studies of optic nerve crush and N-methyl-D-aspartate toxicity model [11,12], it was demonstrated the protective effect of EGCG to the bodies and axons of RGCs, and in the present study, it was further shown that oral administration of EGCG may increase the RGCs survival rates under the damage of high IOP, which might account for the PERG amplitude changes of the open angle glaucoma subjects after EGCG supplementation to a certain extent. However, the current study showed much stronger effects of EGCG on RGC than the clinical trial.…”
Section: Discussionmentioning
confidence: 52%
“…EGCG is a powerful antioxidant exhibiting multifunctional properties [5], including anti-inflammatory [6,7] and vasodilator effects [8], which all contribute to its neuroprotective action [9,10]. In our previous study, it was shown that EGCG led to a protective effect on RGCs in experimental optic nerve crush and N-methyl-D- aspartate toxicity model [11,12]. With these preliminary findings, we investigated the effects of EGCG on counteracting the neurodegenerative damage induced by high IOP.…”
Section: Introductionmentioning
confidence: 98%